ANALISIS KETERPAPARAN INFORMASI DAN KETERSEDIAAN FASILITAS DENGAN KETIDAKBERHASILAN PEMBERIAN ASI EKSKLUSIF PADA IBU BEKERJA - Elfira Nurul Aini; Dian Aby Restanty (JURNAL KESEHATAN INDRA HUSADA, 2022)
Exclusive breastfeeding refers to breastfeeding only and no other food/drink from birth to 6 months of age. Working mothers often fail to provide exclusive breastfeeding. The exclusive breastfeeding coverage rate in the working area of the Kasiyan Health Center is 19.93%, the lowest in Jember Regency. This study was to determine the effect of exposure to information about the inability to provide exclusive breastfeeding with the availability of facilities for mothers who work in the working area of the Kasyan Public Health Center, Jember Regency. This study was included in a quantitative and cross-sectional study on mothers with infants aged 6-12 months who were not exclusively breastfed. The sample size was obtained through purposive sampling technique. The research tool uses a questionnaire. The analysis was performed using a one-sample chi-square statistical test. From the calculation of the analysis results, the p-value of both the availability of facilities and information exposure is 0.000.These results indicate that the availability of facilities and information exposure have a significant effect on the failure of exclusive breastfeeding for working mothers. This proves that the mother has sufficient knowledge about exclusive breastfeeding, but cannot achieve exclusive breastfeeding for 6 months without the support of facilities. In addition to continuous education from health workers, cross-sectoral and cross-program collaboration also needs to be encouraged to increase the success of exclusive breastfeeding among working mothers.